GdCl3 attenuates the glomerular sclerosis of streptozotocin (STZ) induced diabetic rats via inhibiting TGF-β/Smads signal pathway - Jialin Li; Bing Wu; Haibo Hu; Xiansong Fang; Zhiping Liu; Suzhen Wu (Elsevier, 2020)
Diabetic nephropathy (DN) is the most serious end-stage renal disease which characterized by renal glomerular sclerosis including glomerular hypertrophy, glomerular basement membrane (GBM) thickening, mesangial expansion and renal fibrosis. TGF-β/Smads signal pathway plays a crucial role in the development of renal fibrosis. In this study, we found that GdCl3 which was an agonist of Calcium-sensing receptor (CaSR) could repress the activation of TGF-β/Smads signal pathway induced by TGF-β1 or high glucose and then alleviated the accumulation of extracellular matrix (ECM) in mesangial cells and the kidney of type1 diabetic rats. Further study indicated that GdCl3 could induce the binding of CaSR and TβR II and then both of these two receptors translocated from cell membrane to cytoplasm, in this case, TβR II on the cell membrane was decreased and then desensitized to the stimulation of its ligand TGF-β1, so that the activation of its downstream factors such as Smad2 and Smad3 were blocked, finally, ECM expression in mesangial cells were inhibited. We concluded that GdCl3 could alleviate the accumulation of ECM in mesangial cells via antagonizing TGF-β/Smads signal pathway in diabetes mellitus. Keywords: GdCl3, TGF-β/Smads signal pathway, Diabetic nephropathy, Extracellular matrix, Calcium-sensing receptor